VILLAGE WATER GOVERNANCE DALAM PEMENUHAN KEBUTUHAN AIR MINUM DI DESA BETENG POMAH DAN RANDULANANG - Putri Rut Elok Kurniatin; Irfan Ridwan Maksum (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2022)
This research focused on the sustainable governance for meeting the drinking water needs of Beteng, Pomah and Randulanang villages after the end of the PAMSIMAS Program in 2021. After the end of the program, the village government faced several challenges in maintaining basic drinking water services, such as budget limitation, unmaintained quality of drinking water, and the decrease of role and participation of the community and other parties, which caused the gap of the sustainable conditions for meeting clean to safe drinking water needs in these three areas. Through the post positivist approach, assessment of the governance model for meeting drinking water needs in the three villages was conducted to figure out their post-program governance. Through interviews, document studies, and literature, researchers obtained data information as the basis in assessing the governance model in the three villages. The results show that, based on the governance actors and governance styles, the three villages have different governance models even though they participated in the same program (PAMSIMAS). The three villages show different technical dynamics, hence the differences in their governance in realizing the fulfillment of drinking water needs after the end of the PAMSIMAS program.